Worry effect for COVID-19 transmission over depression, anxiety, and satisfaction with studies in Peruvian university students - Mamani-Benito, Oscar; Carranza Esteban, Renzo Felipe; Castillo-Blanco, Ronald; Lingán-Huamán, Susana K.; Gálvez-Díaz, Norma del Carmen; Huancahuire-Vega, Salomón; Corrales-Reyes, Ibraín Enrique (Frontiers in Education, 2023)
Introduction Concern about contracting COVID-19 has had repercussions on university students. The aim of this study was to determine its effect on depression, anxiety, and satisfaction with studies. Methods Using an explanatory cross-sectional design, 1,260 medical, nursing, and dentistry students from both public and private universities in Peru participated in this study. They were assessed using a scale for concern about contracting COVID-19, the Patient Health Questionnaire-2, the Generalized Anxiety Disorder-2 (GAD-2), and a brief scale for satisfaction with their studies. Results After analyzing the data using structural equation modeling, it was found that the explanatory model had an adequate fit. It showed that concern about COVID-19 had a direct and significant effect on anxiety (β = 0.46, p < 0.001) and depression (β = 0.38, p < 0.001). However, the same effect was not evident on satisfaction with studies (β = −0.06, p = 0.068). Discussion The uncertainty about contracting COVID-19 triggered symptoms of anxiety and depression among Peruvian university students. Still, it did not affect the satisfaction students felt when their academic expectations were met.